Improving Student Learning Outcome on Asmaul Husna (Al-Wahab, Al-Alim, and As-Sami) through Problem Based Learning Model - Sugilar, Deni; Mangkuwibawa, Hilman (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to enhance student learning outcomes in Asmaul Husna (Al-Wahab, Al-Alim, and As-Sami) through the Problem-Based Learning (PBL) model. The research method employed is Classroom Action Research (CAR). Observation results indicate significant improvement in both teacher performance and student engagement across cycles. In Cycle I, although some aspects were not fully achieved, teacher performance reached 95%, while student engagement achieved 87.5%. By Cycle II, teacher performance reached 100%, with student engagement at 95%. Learning outcomes also improved, with 56.6% of students achieving mastery in Cycle I, increasing to 86.6% in Cycle II, surpassing the desired mastery level of 85%. This suggests the effectiveness of the PBL model in enhancing student learning outcomes in Asmaul Husna, emphasizing the importance of active learning methods in Islamic education.